2002
DOI: 10.1097/00003226-200211000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Power Calculations After Laser In Situ Keratomileusis

Abstract: Significant refractive errors occurred with each of the methods investigated for determining IOL power after LASIK. RH, CL, or AVG 2 provided the most accurate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
2
35
0
1
Order By: Relevance
“…Our cornea bypass method compares favorably with the results of Randleman et al 1 and Wang et al, 10 who also showed their methods with a similar patient series. Randleman et al 1 used preoperative information with the clinical history method, the contact lens method, or the mean of these 2 methods; the postoperative SE was similar to that in our study (C0.21 D) but the range (ÿ2.25 to C2.25 D) and standard deviation (1.54 D) were much higher. Since their study, the contact lens method has been reported to be unreliable.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Our cornea bypass method compares favorably with the results of Randleman et al 1 and Wang et al, 10 who also showed their methods with a similar patient series. Randleman et al 1 used preoperative information with the clinical history method, the contact lens method, or the mean of these 2 methods; the postoperative SE was similar to that in our study (C0.21 D) but the range (ÿ2.25 to C2.25 D) and standard deviation (1.54 D) were much higher. Since their study, the contact lens method has been reported to be unreliable.…”
Section: Resultssupporting
confidence: 84%
“…2 The inaccuracy of the IOL calculation is caused by inability to accurately measure the corneal power with standard keratometry or videokeratography. 3 Techniques to determine the corneal power include the clinical history and the contact lens methods, as well as the mean of these 2 as described by Randleman et al 1 There have also been more recent techniques such as the modified Maloney method (Maloney RK, personal communication, October 2002) and the topographic central corneal power adjustment method (EffRP adj ) described by Wang et al 3 In this study, a new method to calculate IOL power for patients having cataract surgery after myopic LASIK was developed that ''bypasses'' the need to determine the corneal power. This method is described by Ladas and Stark.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Several reports have been published indicating the high accuracy of this method. Gimbel et al, 4 and Randleman et al, 23 also support the good outcomes for CHM.…”
Section: -13mentioning
confidence: 82%
“…3,4,[19][20][21][22][23] The spherical equivalent change is subtracted from the original corneal refractive power. However, accurate pre-refractive data as well as a stable postoperative refraction are necessary.…”
Section: -13mentioning
confidence: 99%